2016
DOI: 10.1002/2016jd024938
|View full text |Cite
|
Sign up to set email alerts
|

Distinct impact of different types of aerosols on surface solar radiation in China

Abstract: Observations of surface direct solar radiation (DSR) and visibility, particulate matter with aerodynamic diameters less than 2.5 µm (PM2.5), together with the aerosol optical thickness (AOT) taken from Moderate‐Resolution Imaging Spectroradiometer and Multiangle Imaging Spectroradiometer, were investigated to gain insight into the impact of aerosol pollution on surface solar radiation in China. The surface DSR decreased during 2004–2014 compared with 1993~2003 over eastern China, but no clear reduction was obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
72
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 143 publications
(74 citation statements)
references
References 59 publications
2
72
0
Order By: Relevance
“…To eliminate the contamination of cloud and precipitation, data samples under cloudy (CF ≥ 0.1) or rainy conditions (TP > 0) are removed. In agreement with Yang et al (2016), we note that even with this limitation, some days with few broken clouds (CF < 0.1) still can introduce additional uncertainties to our study. The PBLHs are extracted from the European Centre for Medium-Range Weather Forecasts (ECMWF) interim reanalysis (ERA-Interim; Dee et al, 2011), with a horizontal resolution of 0.125 • × 0.125 • and 3 h temporal resolution.…”
Section: Meteorological Datasupporting
confidence: 66%
See 1 more Smart Citation
“…To eliminate the contamination of cloud and precipitation, data samples under cloudy (CF ≥ 0.1) or rainy conditions (TP > 0) are removed. In agreement with Yang et al (2016), we note that even with this limitation, some days with few broken clouds (CF < 0.1) still can introduce additional uncertainties to our study. The PBLHs are extracted from the European Centre for Medium-Range Weather Forecasts (ECMWF) interim reanalysis (ERA-Interim; Dee et al, 2011), with a horizontal resolution of 0.125 • × 0.125 • and 3 h temporal resolution.…”
Section: Meteorological Datasupporting
confidence: 66%
“…The direct effect of aerosol on radiation refers to the scattering and absorption of the solar and longwave radiation by aerosol (Charlson et al, 1992;Koren et al, 2004;Lohmann and Feichter, 2005;Qian et al, 2007;Li et al, 2011;Huang et al, 2014;Yang et al, 2016) and the indirect effect of aerosol on radiation is associated with changes in the cloud macro-and micro-physical properties caused by aerosol which can serve as cloud condensation nuclei or ice nuclei (Twomey, 1977;Albrecht, 1989;Kaufman and Fraser, 1997;Feingold, 2003;Garrett et al, 2004;Gar-rett and Zhao, 2006;Zhao et al, 2012;Hoose and Möhler, 2012;Liu et al, 2012;Zhao and Garrett, 2015). The radiative effect of aerosol is relatively large due to increased emissions of pollution in East Asia (Wang et al, 2010a;Zhuang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Such kind of effect was named as the "dome effect" of BC . Similar effect has also been found for BC over the Indian Ocean (Wilcox et al, 2016), and dust aerosols in northern and eastern China Yang et al, 2016).…”
Section: Introductionsupporting
confidence: 58%
“…Another observation‐based estimation by Yang et al () found that the ADR effect can strengthen the total aerosol amount by ~12% and ~15% through reductions in the near‐surface wind and BLH in Beijing, respectively, which are even larger than model simulation results. Yang et al () further analyzed the sensitivity of the ADR effect to aerosol type in China and found that the net effects of aerosols on the surface solar radiation and corresponding climatic effects are dependent on both the aerosol amount and optical properties. Note that the aforementioned studies are mostly of short duration.…”
Section: Aerosol Formation Nucleation Optical Properties and Radiamentioning
confidence: 99%